Laporan Kasus: Hepatitis B pada Ibu Hamil yang Terdeteksi Melalui Triple Elimination Screening di Fasilitas Pelayanan Primer - Susi Elvina Sari; Cut Khairunnisa (Lembaga Pengembangan Kinerja Dosen, 2025)
A 37-year-old woman, G3P2A0, at 16 weeks of gestation, came to the community health center for her first antenatal check-up. The patient had no characteristic clinical symptoms, but the triple elimination screening results showed reactivity for HBsAg, with negative HIV and syphilis results. An ultrasound examination revealed a viable intrauterine fetus with normal findings. The patient had not received Hepatitis B immunization or vitamin supplements previously, and the patient's partner had not undergone Hepatitis B screening despite having a work-related risk factor. The patient was given iron and vitamin supplements and referred to the hospital for further evaluation. Comprehensive education was provided regarding modes of transmission, risks of maternal and fetal infection, prevention of vertical transmission, as well as the importance of Hepatitis B immunization and the administration of HBIG to the newborn within 12 hours after birth. This case emphasizes the importance of early antenatal screening, comprehensive education, psychosocial support, and collaboration between the patient, family, and healthcare providers to prevent vertical transmission of Hepatitis B. The education provided included essential preventive measures and infection control steps to protect both the mother and the baby. Proper management and follow-up monitoring are necessary to ensure the health of the mother and baby and prevent further complications.